2015
DOI: 10.1111/pim.12220
|View full text |Cite
|
Sign up to set email alerts
|

Administration of naloxone in combination with recombinant Plasmodium vivax AMA‐1 in BALB/c mice induces mixed Th1/Th2 immune responses

Abstract: Naloxone (NLX) has the ability to shift the immune response to a Th1 profile. Therefore, the adjuvant efficacy of NLX with recombinant P. vivax apical membrane antigen-1(rPvAMA-1) in BALB/c mice was evaluated. Mice were immunized subcutaneously with purified rPvAMA-1 formulated with NLX (doses of 5 mg/kg body weight) alone or in combination with IFA. A significant increase in anti-PvAMA-1 IgG antibody after the second boost (mean OD = 2·08 and 2·17, in groups received, rPvAMA-1/NLX and rPvAMA-1/NLX/IFA, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
3
1
Order By: Relevance
“…Therefore, it can generally be concluded that for shifting immune responses to strong and specific Th1 response to PvTRAP, adjuvants MPL, CpG, and to a lesser extent, to NLX are suitable. Interestingly, this finding is in contrast to a previous work [56] in which NLX together with rPvAMA-1 could induce mixed Th1/Th2 responses; however, this adjuvant with rPvTRAP produced more Th1 than Th2 responses, suggesting a role for the nature of antigen in the immune responses. The immune sera from mice vaccinated with the rPvTRAP/adjuvants groups exhibited IgG antibody with the high avidity on days 38 and 180 of first immunization, which is likely due to the maturation of immune response and the selection of clonal B-cells that result in IgG avidity increases [65].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can generally be concluded that for shifting immune responses to strong and specific Th1 response to PvTRAP, adjuvants MPL, CpG, and to a lesser extent, to NLX are suitable. Interestingly, this finding is in contrast to a previous work [56] in which NLX together with rPvAMA-1 could induce mixed Th1/Th2 responses; however, this adjuvant with rPvTRAP produced more Th1 than Th2 responses, suggesting a role for the nature of antigen in the immune responses. The immune sera from mice vaccinated with the rPvTRAP/adjuvants groups exhibited IgG antibody with the high avidity on days 38 and 180 of first immunization, which is likely due to the maturation of immune response and the selection of clonal B-cells that result in IgG avidity increases [65].…”
Section: Discussioncontrasting
confidence: 99%
“…Immunized mouse sera were evaluated for anti-rPvTRAPspecific antibodies by ELISA as described previously [56] with some modifications. Briefly, rPvTRAP protein (50 ng/ well) was diluted in a coating buffer (0.06 M Na 2 CO 3 / NaHCO 3 , pH 9.6), coated in Maxisorp flat-bottom 96-well ELISA plates (Jet Biofil) and kept at 4 °C overnight.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Both Th1 and Th2 cells can express the β1 chain of the IL-12 receptor, but only Th1 cells can express the β2 chain. Th2 cells without β2 chain could not be directly transformed into Th1 cells ( 36 ), but Th1 cells could be transformed into Th2 cells ( 37 ). These results indicate that the shift from Th1 to Th2 induced by E. Multilocularis infection would cause immunosuppression of the host and thus allow E. Multilocularis to escape from the immune system and continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against PvAMA-1 have an invasion inhibitory role against diverse P. vivax strains (212). Someabozorg et al (213) demonstrated that naloxone (NLX) alone as an adjuvant in a vaccine formulation with recombinant PvAMA-1 cannot induce a good immune response. However, in combination with another adjuvant, such as IFA, a balanced Th1/Th2 response was obtained (213).…”
Section: Pvama-1mentioning
confidence: 99%